Suicide ideation, behavior and suicide intent of alcohol dependent patients - Dilbaz, Nesrin; Aytekin, Yafer (Journal of Dependence, 2003)
Objective: The percentage of the completed suicide among alcohol and substance dependent patients is approximately 25%. Also, alcohol dependence is one of the most important factors that increase the tendency of suicide for adults. In present study, the frequency of lifetime suicide attempts, the characteristics of suicide attempts, and the level of hopelessness, suicide ideation suicide behavior and intent were evaluated.Method: Suicide history questionnaire that inquires socio-demographic and suicide characteristics, Beck Depression and Hopelessness Scale, Suicide Ideation and Suicide Behavior Scale were given to the study group which included 50 consecutive alcohol dependent patients that fulfilled the study including criteria and that hospitalized for detoxification program. A computer program known as statistical package for social sciences (SPSS) program was used to compare the data of patients that had attempted suicide with unattempted patients.Results: The frequency of attempted suicide for lifetime was determined as 26%. According to the results of the present study, physical punishment history and the risk of repeated attempts were more frequent among suicide attempters. Drug and/or chemical substance ingestion were the most frequent method for suicide. Most of the patients stated that suicide attempts were impulsive, but they also admitted that they had told about their plan before attempt. The most frequent recent life event that causes suicide attempt was family problems. Beside this we determined that hopelessness and depression level is closely related with suicide attempt. We can also concluded that while suicide ideation, suicide behavior and to suicide intent is becoming more evident; the tendency for suicide attempt becomes more marked.Conclusion: The professionals that study with alcohol dependent patients must focus on the risk of attempted suicide among alcohol dependent group because the frequency of lifetime attempted suicide is higher among this group.
Keywords: Alcohol dependence; suicide; clinical features